Durable response to Olaparib in EGFR and somatic BRCA2-mutated lung adenocarcinoma with leptomeningeal metastases: a case report - Hou, Fang-fang; Liu, Li-rong; Zhao, Wen-jie; Qu, Yan-chun; Zhou, Rui; Wang, Tian-lin; Ye, Yong-song; Chai, Xiao-shu; Zhang, Hai-bo (Frontiers in Oncology, 2025)
Mutations in breast cancer susceptibility genes 1/2 (BRCA1/2) are strongly associated with a significantly higher risk of numerous cancers, including ovarian, breast, prostate, and pancreatic cancer. PARP inhibitors have been approved for the treatment of ovarian and breast cancer. However, studies focusing on the association between the BRCA gene and NSCLC, as well as the efficacy of PARP inhibitors in NSCLC, are scarce. Here, we present the case of a patient with lung adenocarcinoma harboring EGFR and somatic BRCA2 mutations, who developed resistance to third-generation EGFR tyrosine kinase inhibitors (TKIs) and subsequently exhibited durable response to Olaparib. This case exemplifies the remarkable efficacy of precision-targeted therapy in combination with intrathecal chemotherapy, which has resulted in significant clinical improvement for an EGFR- and BRCA-mutant lung cancer patient suffering from severe and symptomatic leptomeningeal metastases. Our findings provide clinical evidence and guidance for the treatment of NSCLC patients with BRCA mutations. Nonetheless, further studies are warranted to elucidate the role of BRCA mutations in NSCLC.